Hidden Hunger : Gender and the Politics of Smarter Foods - Kimura, Aya Hirata, 1974- (Book collections on Project MUSE., 2013)
Uncovering hidden hunger -- Charismatic nutrients -- Solving hidden hunger with fortified food -- Bound by the global and national : Indonesia's changing food policies -- Building a healthy Indonesia with flour, MSG, and instant noodles -- Smart baby food : participating in the market from the cradle -- Creating needs for golden rice.